2003
DOI: 10.1097/00019605-200304000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Congenital ptosis with esotropia in brothers

Abstract: Two brothers are reported with congenital ptosis and esotropia, one of whom also has polythelia. This particular constellation of clinical features has not previously been described, although comparison with recorded families does show significant overlap with the pedigree reported by Frydman et al.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…In 2002, there has been a report of two brothers having congenital ptosis with esotropia with a pedigree similar to that reported by Frydman et al; however, unlike FCKS both had undescended testis and one had polythelia. 4 To our knowledge, this is the first reported case of FCKS in Asia.…”
Section: Descriptionmentioning
confidence: 70%
“…In 2002, there has been a report of two brothers having congenital ptosis with esotropia with a pedigree similar to that reported by Frydman et al; however, unlike FCKS both had undescended testis and one had polythelia. 4 To our knowledge, this is the first reported case of FCKS in Asia.…”
Section: Descriptionmentioning
confidence: 70%
“…Writing in these pages, Madasseri et al, (2003) reported brothers, aged 7 and 1 years at the time of examination who presented with congenital ptosis and esotropia. No developmental concerns were noticed.…”
mentioning
confidence: 99%